2002
DOI: 10.1016/s0022-2275(20)30108-5
|View full text |Cite
|
Sign up to set email alerts
|

Bisphenol A in combination with insulin can accelerate the conversion of 3T3-L1 fibroblasts to adipocytes

Abstract: The confluent cultures of 3T3-L1 fibroblasts were treated with or without bisphenol A (BPA) for 2 days and subsequently treated with insulin (INS) alone for 9 days. When BPA was absent during the first 2-day treatment period, the cultures contained 1.6 g/ g DNA of triacylglycerol (TG), 202 mU/mg DNA of lipoprotein lipase (LPL) activity, and 462 nmol/min/mg DNA of glycerol-3-phosphate dehydrogenase (GPDH) activity. The presence of BPA during the same period caused a 150% increase in the TG content, a 60% increa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 206 publications
(28 citation statements)
references
References 47 publications
0
26
0
2
Order By: Relevance
“…The expression of PPARγ, C/EBPα, and LPL was upregulated in abdominal adipocytes of adult female rats. Masuno et al (2001) reported that BPA can increase the activity of LPL and the accumulation of TG in 3T3-L1 cells, leading to its differentiation into adipocytes with larger lipid droplets [ 66 ]. The staining of tissue sections in this study also yielded similar results ( Figure 1 and Figure 2 ).…”
Section: Discussionmentioning
confidence: 99%
“…The expression of PPARγ, C/EBPα, and LPL was upregulated in abdominal adipocytes of adult female rats. Masuno et al (2001) reported that BPA can increase the activity of LPL and the accumulation of TG in 3T3-L1 cells, leading to its differentiation into adipocytes with larger lipid droplets [ 66 ]. The staining of tissue sections in this study also yielded similar results ( Figure 1 and Figure 2 ).…”
Section: Discussionmentioning
confidence: 99%
“…Some EDCs influence gene expression, including expression of genes related to lipid storage [ 15 , 16 ]. Tributyltin also has epigenetic effects [ 29 ], although it is unknown if these effects extend to genes related to lipid accumulation.…”
Section: Discussionmentioning
confidence: 99%
“…Many of these chemicals work indirectly through epigenetic mechanisms by affecting key genes linked to obesity. Specifically, phthalate esters such as bisphenol-a and mono-(2-ethylhexyl) phthalate upregulate adipocyte or lipogenic genes which can lead to obese phenotypes [ 15 , 16 ]. Additionally, EDCs can act directly on the HPT axis by altering levels of circulating thyroid hormones (triiodothyronine [T 3 ] and thyroxine [T 4 ]) which regulate, among other things, lipid metabolism [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…In contrast from the foregoing, a finding revealed that chronic BPA administration to rats for 3 months did not bring about a change in body weight, fat storage or a rise in triglyceride level [3]. It was also revealed that by utilizing 3T3-F442A, adipocytes and BPA invigorated insulin-dependent glucose uptake with augmented Glut4 expression in an animal model [4][5][6].…”
Section: DImentioning
confidence: 92%